EFEKTIFITAS PROMOSI KESEHATAN TERHADAP TINGKAT PENGETAHUAN HIV PADA REMAJA DI SMAK RANTEPAO, SULAWESI - siska evi martina (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2019)
Knowledge of HIV had been lacking among adolescents and adolescents are particularly vulnerable to HIV infection. Globally, the prevalence of HIV remains on the rise especially among adolescents who are at increased risk of infection. The purpose of this study was to examine the effect of health promotion on HIV knowledge among the student of Catholic High School in Rantepao, Toraja Utara Sulawesi Selatan by Quasi Experimental. Fifty-nine students recruited from Catholic High School in Rantepao, Toraja Utara Sulawesi Selatan by simple random sampling. Data were analyzed using Dependent t-test and Multiple linear regression. The results indicated that after participating in health promotion, there was a significant improvement in HIV knowledge in the experimental group which was shown by significant difference in mean score of HIV knowledge before intervention (X12,68), after intervention ( X 28.86), p< 0.00. In addition, Multiple linear regression showed that health promotion was a significant effect in HIV knowledge (p, 0.07). This HIV health promotion appears to be effective in improving HIV knowledge among adolescents in Catholic High School in Rantepao, Sulawesi.